Synthesis of Novel Azetidinone and Thiazolidinones Derivatives and Evaluation of Their Antimicrobial Efficacy - K. H. Patel; A. G. Mehta (E-Journal of Chemistry)
2-Amino-4-(2-naphthalenyl) thiazole (1) was prepared from 2-acetylnapthalene. This amine on facile condensation with aromatic aldehydes afford Schiff Base/anils/azomethines(2a-h). These anils on cyclocondensation reaction with chloro acetyl chloride and thio glycolic acid (i.e. mercapto acetic acid) yields 2-azetidinones and 4-thiazolidinones respectively. The prepared compounds have been screened on some stains of bacteria.